The wages of destruction : the making and breaking of the Nazi economy - Tooze, J. Adam 1967- (Penguin Books, 2006)
Introduction -- Pt. 1. RECOVERY. 'Every worker his work' -- Breaking away -- Partners : The regime and German business -- Volksgemeinschaft on a budget -- Saving the peasants -- Pt. 2. WAR IN EUROPE. 1936 : Four years to war -- Into the danger zone -- 1939 : Nothing to gain by waiting -- Going for broke : The first winter of war -- Victory in the West - Sieg im Westen -- Britain and America : Hitler's strategic dilemma -- Pt. 3. WORLD WAR. Preparing for two wars on once -- The grand strategy of racial war -- December 1941 : Turning point -- Labour, food and genocide -- Albert Speer : 'Miracle man' -- No room for doubt -- Disintegration -- The end -- Appendix : Supplementary data